Політичне переслідування як соціально-правовий феномен: кримінологічний аспект - Орлов, Ю. В.; Orlov, Y. V.; Орлов Юрій Володимирович (Право і безпека. - 2015. - № 2 (57). - С. 120-126., 2015)
Досліджено політичні переслідування як кримінологічно значущі фактори та форми відтворення політичної злочинності. Запропоновано авторське поняття категорії «політичне переслідування». Відстоюється думка, що воно може бути двох видів: політико-правове та політико-дискримінаційне. Викладено вузьке та широке розуміння останнього. Перше відображає діяльнісну природу переслідування, друге – структурно-функціональну. Політико-дискримінаційне переслідування диеренційоване на цілераціональне, цінніснораціональне та корпоративно-узвичаєне.

In order to determine the social and legal nature, the concept and types of political persecution, as well as realizing a short criminological analysis of the features of its reconstitution the author has studied political persecutions as important in criminology factors and forms of reconstitution of political crime. The object of the study was political persecution as a social and legal phenomenon. Research methodology is represented by three levels of cognition. Epistemological tools of dialectical determinism are used on the philosophical level. A number of methods of formal logic and comparison, modeling are used on general and scientific level. Not included sociological observation, content analysis of mass media materials, media, litigation, expert evaluations are used on special and scientific level. Under political persecution the author has suggested to understand activity that is based on using legal and / or illegal diverse, functionally joint measures of impact on a person (or group of people), which are united by political or politically conditioned purpose and which entail social encumbrance and / or cause physical, moral or material damage. This concept encompasses political and legal, political and discriminatory persecution. In the narrow, behavior understanding political and discriminatory persecution appears as a kind of political persecution that is a manifestation of discrimination of an individual or groups on the basis of their political activity or political views of certain content. Depending on the specific internal determination political and discriminatory persecution is differentiated into instrumentally rational, value and corporate commonly accepted. Broadly, according to structural and functional sense political and discriminatory persecution is a tool for constructing public and political thought or control in the sphere of political and corporate management, which is used to preserve the stability of the political situation and / or consolidation of political forces and / or provision of its local dominance in the political confrontation.

Исследованы политические преследования как криминологически значимые факторы и формы воспроизводства политической преступности. Предложено авторское понятие категории «политическое преследование». Отстаивается мнение, что оно может быть двух видов: политико-правовое и политико-дискриминационное. Приведены узкое и широкое понимание последнего. Первое отражает деятельностную природу преследования, второе – структурно-функциональную. Политико-дискриминационное преследование дифференцированно на целерациональное, ценностнорациональное и корпоративно-традиционное.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; політичне переслідування; дискримінація; злочинність; political persecution; discrimination; crime; политическое преследование; дискриминация; преступность